Studies of EC pre-ionization in DIII-D to support development of ITER plasma initiation. (1st June 2022) - Sinha, J.; de Vries, P.C.; Walker, M.L.; Battaglia, D.J.; Turco, F.; Hyatt, A.; Kim, H.T.; Stober, J.; Yoneda, R.; Gribov, Y.; Haskey, S.R.; Bykov, I.; et al.
Abstract: New experiments have been conducted at DIII-D to improve the physics understanding of plasma initiation assisted by electron cyclotron (EC) wave injection, allowing better extrapolation to ITER. This has been achieved by applying an EC pulse prior to start of the inductive plasma initiation (i.e. the generation of a loop voltage). A pre-plasma was formed during the EC pulse that was characterized in terms of the maximum density and temperature. Parametric scans were performed to study the influence of the EC injected power, EC injection angle, and pre-fill gas pressure on the pre-plasma creation process. These experiments showed that pre-ionized plasma of good quality can have a significant effect on the subsequent V loop induced plasma initiation process, i.e. a high density pre-plasma, increases the plasma current rise and speed at which ionization is achieved when the V loop is applied. A good quality pre-plasma is one that achieved a significant degree of ionization, mainly obtained by providing sufficient ECH power in DIII-D of the order of 1 MW. It was found that a minimum EC power of 0.5 MW was required in DIII-D to create ionization, and this would scale to a minimum power of roughly 6.5 MW for ITER.